An Exploration of Fitting Start-Up Incubator for University Students in Bandung - Akbar, Muhammad Fikri; Aldianto, Leo (Journal of Innovation, Business and Entrepreneurship, 2017)
Abstract- One of the issue that correlate with better better economy in a country is how they could develop startup founder from university students. In United States, one of the most developed startup country in the world, the push to create more and more high-tech startup from the youth has been rising. With the research that showded how high-tech startup could increace employment rate,Â  new high-tech startup are expected to be produced from university students as the youth who have many potential. Apparently in India, the country with similar demographic to Indonesia, who will have mass population of young people, already in the move to follow the footstep of United States. They already implement student startup policy, a policy with ambitious vision of producing 100,000 tech startup from 10,000 university across the country by providing program such as incubator for students. This research try to explore how is the current condition in Indonesia, spesifically in the case of Bandung, which have more than 100 university in the cities. This research wanted to explore from the existing startup incubator in Bandung and how are the university students who are interested on becoming startup founder see them. By getting the insight on how is the perspective, challenges, and suggestion from both side, this research try to find a recommendation on creating fitting startup incubator for university students that could help development of future potential of university student founder just like othe countries. The findings of this reseach found out that currently it is unlikely to provide a startup incubator program that target univerasity student if the provider/incubator is not backed up by university/government/big corporate which could provide vast resource to face the uncertainty of incubating students. The big problem that made it hard is the commitments issue that is agreed by the incubators and the students themselves. Thus this research recommend that in current condition the better way is to provide program in a form that resemble pre-incubation phase, which focus on giving open experience to the students with the goal tofilter the one who is commited and then after that the incubation phase could started.Â Keywords : Startup, Incubator, University Students, commitment